Three new Hemienchytraeus species (Enchytraeidae, Oligochaeta, Annelida) from Korea, with first records of other enchytraeids and terrestrial polychaetes (Annelida) - Dózsa-Farkas, Klára; Hong, Yong (Zootaxa, 2010)
This is the first occasion that the enchytraeid (Enchytraeidae, Oligochaeta) fauna has been investigated in Korea. 18 enchytraeid taxa (7 genera) and two terrestrial polychaetes (Hrabeiella sp. and Parergodrilus heideri) were identified. Three species are new to science (Hemienchytraeus koreanus sp. n., H. jeonjuensis sp. n. and H. quadratus sp. n.); they are described here. Twelve taxa were distinguished at species level, four of them are cosmopolitan widespread species in the Holarctic, and one, Enchytraeus irregularis is obviously an introduced species. The two polychaetes were known previously only from Europe.